TNFα antagonist in combination with PD-1 blocker to prevent or retard malignant transformation of B[a]P-induced chronic lung inflammation. (1st March 2022) - Zhao, Ai; Li, Fanfan; Wei, Cheng; Zhou, Zhujun; Luo, Xianqiang; Wu, Haiming; Ning, Chunhong; Liu, Wanyu; Li, Dong; Lin, Danni; Liu, Shuwen; Zhang, Guangji; et al.
Abstract: Benzo[a]pyrene (B[a]P) is a typical complete carcinogen in tobacco, but its mechanism of inducing the development of chronic pneumonia and consequent lung cancer is unclear. Here we elucidated the role of myeloid-derived suppressor cells (MDSCs) in developing B[a]P-induced chronic lung inflammation and efficacy of immunotherapy in preventing subsequent malignant transformation. Our study showed that as B[a]P could induce the accumulation of MDSCs in lung tissues and enhance the immunosuppressive effect regulated by cytokines and metabolites, thereby promoting the formation of immunosuppressive microenvironment, where effector T cells were exhausted, NK cells were dysfunctional, regulatory T (Treg) cells were expanded, polarized alveolar macrophages were transformed from M1 to M2. Subsequently, we performed the immunotherapy to block TNFɑ only or both TNFɑ and PD-1 at the early- or middle-stage of B[a]P-induced chronic lung inflammation to ameliorate the immunosuppressive microenvironment. We found that TNFɑ antagonist alone or with PD-1 blocker was shown to exert therapeutic effects on malignant transformation at the early stage of B[a]P-induced chronic lung inflammation. Taken together, our findings demonstrated that B[a]P-induced chronic lung inflammation resulted in the accumulation of MDSCs in lung tissues and exercise their immunosuppressive functions, thereby developing an immunosuppressive microenvironment, thus TNFɑ antagonist alone or with PD-1 blocker could prevent or retard the malignant transformation of B[a]P-induced chronic lung inflammation. Graphical Abstract: